Step up Eketahuna LLC ; Summit Entertainment ; Touchstone Pictures ; produced by Erik Feig, Jennifer Gibgot, Adam Shankman, Patrick Wachsberger ; story by Duane Adler ; screenplay by Duane Adler and Melissa Rosenberg ; directed by Anne Fletcher. - Tatum, Channing 1980-; Fletcher, Anne 1966-; Dewan, Jenna 1980-; Radcliff, Damaine 1979-; Washington, De'Shawn; Seresin, Michael 1942-; Zigman, Aaron 1963- (D'Concorde Recording Corp., 2006)
Tyler is a rebel from the wrong side of Baltimore¹s tracks. The only thing that stands between him and an unfulfilled life are his dreams of one day making it out of there. Nora is a privileged ballet dancer attending an elite school of dance in Baltimore. The only thing standing in the way of her brilliant future is finding a great dance partner for her senior showcase. When trouble with the law lands Tyler with a community service gig at Maryland School of the Arts, he arrives as an angry outsider, until his skills as a gifted street dancer draw Nora¹s attention. With sparks flying on and off stage, Tyler realizes he has just one performance to prove that he can step up to a life far larger than he ever imagined.